3(x-8)=-9x+12

Simple and best practice solution for 3(x-8)=-9x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-8)=-9x+12 equation:


Simplifying
3(x + -8) = -9x + 12

Reorder the terms:
3(-8 + x) = -9x + 12
(-8 * 3 + x * 3) = -9x + 12
(-24 + 3x) = -9x + 12

Reorder the terms:
-24 + 3x = 12 + -9x

Solving
-24 + 3x = 12 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-24 + 3x + 9x = 12 + -9x + 9x

Combine like terms: 3x + 9x = 12x
-24 + 12x = 12 + -9x + 9x

Combine like terms: -9x + 9x = 0
-24 + 12x = 12 + 0
-24 + 12x = 12

Add '24' to each side of the equation.
-24 + 24 + 12x = 12 + 24

Combine like terms: -24 + 24 = 0
0 + 12x = 12 + 24
12x = 12 + 24

Combine like terms: 12 + 24 = 36
12x = 36

Divide each side by '12'.
x = 3

Simplifying
x = 3

See similar equations:

| 10t-11=7t-5 | | 3.3x-11.26=5.9 | | -6x-2=(3x^2+1) | | 180=28x+(x*x) | | X(4X-8)=(4X+5)(x-2) | | 9+(9+x)+(9+.5(9+x))=9+(9+x)+(9+.5(9+x)) | | 3(x+5)=2(4x+10) | | 2(x-2)=60-(1-x) | | 14=0.8x | | 3x+3x+4x-30=180 | | 5y(2x-1)=y(x+2)+20 | | 2.9x-18.31=7.5 | | x^2+22x-40=0 | | 2.2x-15.18=3.3 | | 7m-4-2m=13 | | 3.5=3(4+.5r) | | X^4-8x^3+23x^2-28x+11=0 | | x-.3x=56000 | | x+.3x=56000 | | 3.5r=3(4+.5) | | y=3x^500+15x^100 | | 3.5r=3(4+5) | | 9-10+11q=-30 | | 144=9(2x-17) | | x+6y=155 | | 3.3x-11.26=59 | | 2x-3(2x)=12 | | 3x+3y=540 | | 4x-x+2=5-x | | 45x^3-500x=0 | | 4x^3-36x^2-x+9=0 | | x^7+x^5-25x^3-25x=0 |

Equations solver categories